2022
DOI: 10.3390/su142114549
|View full text |Cite
|
Sign up to set email alerts
|

Developing AI Literacy for Primary and Middle School Teachers in China: Based on a Structural Equation Modeling Analysis

Abstract: As smart technology promotes the development of various industries, artificial intelligence (AI) has also become an important driving force for innovation and transformation in education. For teachers, how to skillfully apply AI in teaching and improve their AI literacy has become a necessary goal for their sustainable professional development. This research examines the correlations among the dimensions of AI literacy of teachers in order to promote the effectiveness of class teaching and the adoption of arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 64 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The study indicates that many teachers view AI as a valuable supplementary tool for enhancing education, resonating with the broader trend of recognizing the potential benefits of technology in education. This sentiment is further supported by the research of Chiu et al (2022) and Zhao et al (2022), emphasizing the need to explore the development of AI literacy for teachers in diverse educational contexts. The study also reinforced the consistent positive perception of AI across different experience levels and academic backgrounds (Chiu & Chai, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…The study indicates that many teachers view AI as a valuable supplementary tool for enhancing education, resonating with the broader trend of recognizing the potential benefits of technology in education. This sentiment is further supported by the research of Chiu et al (2022) and Zhao et al (2022), emphasizing the need to explore the development of AI literacy for teachers in diverse educational contexts. The study also reinforced the consistent positive perception of AI across different experience levels and academic backgrounds (Chiu & Chai, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, they advocated for the adoption of a teaching achievement model as a theoretical perspective to guide educators and researchers in leveraging teaching activity data to enhance teaching quality ( Ndukwe & Daniel, 2020 ). Zhao, Wu & Luo (2022) scrutinized the correlation between dimensions of teachers’ AI literacy, aiming to enhance the efficacy of classroom teaching and the integration of AI literacy. Their assessment encompassed teachers’ AI literacy levels, covering aspects such as knowledge and understanding of AI, AI application, evaluation of AI application, and AI ethics.…”
Section: Discussionmentioning
confidence: 99%
“…Their assessment encompassed teachers’ AI literacy levels, covering aspects such as knowledge and understanding of AI, AI application, evaluation of AI application, and AI ethics. Findings indicated that AI applications significantly positively influenced the other three dimensions ( Zhao, Wu & Luo, 2022 ). Additionally, Chen et al (2022) employed a structural equation model and fuzzy set for qualitative comparative analysis to investigate the impact of school information and communication technology (ICT) infrastructure and teachers’ information literacy on teacher burnout.…”
Section: Discussionmentioning
confidence: 99%
“…By incorporating AI topics into the curriculum, educators can equip students with the knowledge and skills they need to navigate the challenges and opportunities presented by AI. However, for such initiatives to be successful, teachers themselves must be empowered with AI knowledge and literacy (Zhao et al, 2022). Developing teachers' understanding of AI, its applications, and its implications is essential for fostering a learning environment that encourages innovation, critical thinking, and ethical reasoning.…”
Section: Introductionmentioning
confidence: 99%